Implementation of Digital Leadership in Primary School - Wijayanti, Dian Marta; Pramono, Suwito Eko; Handoyo, Eko; Sugi, Sugi (Proceedings of International Conference on Science, Education, and Technology, 2024)
Leadership in the 21st century must capably utilize technology to increase school quality. Various demands work not regardless of digital technology. Because of that, the principals must control digital skills in carrying out school management. The purpose of this research is to describe the implementation of digital leadership by head of Guru Penggerak Programme. The principal that was assigned from Guru Penggerak programme believe the capable become a pioneer of educational transformation. The method used in this research is qualitative descriptive design at 6 elementary schools (SD), namely SDN Lamper Lor, SDN Jabungan, SDN Jatibarang 03, SDN Pakintelan 02 , SDN Kuningan 03, and SDN Karangroto 04. Data collection was carried out through interviews with headmaster. The findings of this research show that six schools led by principals from Guru Penggerak Programme graduates have implemented digital leadership as an effort to achieve educational transformation. The achievements that have been made include seven pillars of digital leadership, namely student engagement and learning, student spaces and environment, professional learning and growth, communication, public relations, branding, and opportunity . This research provides contribution importance digital leadership applied in school’s base. As unit education that is not own power administration specifically , a principal want to study for control technology information. A number of the way it is done by school principals through digital platforms, learn through community practitioners, and study from YouTube for learn knowledge new education.